Mechanical properties of additively manufactured kraft paper lattices and paper-epoxy interpenetrating phase composites for polymer foam replacement - Lim, Guo Yao (2024)
In an effort to reduce pollution by polymer wastes, cellulose paper is investigated as a polymer foam replacement for structural applications. Closed-cell plate lattices, open-cell truss lattices, honeycombs and epoxy-paper interpenetrating phase composites (IPC) were fabricated using a sheet lamination technique. The microstructures of both paper and IPC samples were examined using scanning electron microscopy and gas pycnometry. Modulus, strength and energy absorption of the structures were characterized with quasistatic compression test (strain rate = 0.2/s). To analyse the buckling behavior of different lattice geometries, finite element simulations were performed and the obtained results were validated with the captured deformation images. Under mechanical loading, it was observed that the lattices failed by kinking in the isostrain orientation while they generally failed by buckling in the isostress orientation. It was postulated that these failure modes minimized shear stresses between the sheets and were, therefore, preferred. Because the fibers were aligned to the load axis in the isostrain orientation, lattices were stiffer. Conversely, finite element simulations indicate that stresses were better distributed in the isostress orientation and hence, such lattices were stronger. The addition of epoxy matrix into an Octet Truss paper lattice increased its specific stiffness, specific strength and isotropy significantly. Other than acting as supports to reduce bending of the diagonal struts, epoxy was found to infiltrate into the space between kraft paper fibers, forming a fiber-reinforced composite that conferred an excellent bond to the paper lattice and epoxy. The paper-based structures were also found to collectively exhibit an energy absorption efficiency of 31 % (i.e. cushion factor ∼3), comparable to elastomeric polymer lattices. Further benchmarking against literature values indicate that the specific modulus, specific strength and volumetric energy absorption of the additively manufactured paper-based structures were either comparable or superior to most polymer foams, suggesting that such paper-based structures are viable green substitutes for polymer foams.